Pengaruh Neuro Developmental Treatment Terhadap Kemampuan Gross Motor Berdiri Anak Cerebral Palsy Spastik Diplegi - Anwar, Ervyandinata Iskha, Edy Wapada, SST.Ft, M.Kes (2017)
Background: Cerebral palsy is a group of permanent disorders in the development of movement and posture due to the limitations of the activity associated with non-progressive disorder that occurs in the brains of developing fetuses and infants. Diplegi is the paralysis that accompanies all limbs but usually the upper limbs is lower than the lower limbs. The prevalence of CP according to the Basic Health Research (RIKESDAS) in children aged 24-59 months in 2010 amounted to 0.09% of the total number of births in Indonesia, Based on these issues, physiotherapy as health workers play a role in dealing with children with cerebral palsy spastic diplegi purpose to improve the function of the motion members so that children can grow and develop properly. This study authors used a neuro developmental treatment modalities such as inhibition and facilitation, neuro developmental interverensi treatment is most often used for children with developmental disorders, especially in the case of cerebral palsy. Objective: Determine the influence of neuro developmental treatment on the ability of the motor gross stand diplegi spastic cerebral palsy children. Method: This research is Quasi Experimental. The design study is "one group pre and post design". In this study, respondents were taken as many as 10 children and all of them carried out the treatment using a measuring instrument gross measure ofmotorfunction(GMFM). Results: Statistical test results using Wilcoxon Test p value is p <0.05 (p = 0.034), data and from Wilcoxon test obtained Z count = 2,121 and Z table Z = 0.0166 So Z count> Z table, then the effect there significant gross motor children Standing before and after treatment given. Conclusion: There is a neuro developmental effects of treatment on the ability of the motor gross stand diplegi spastic cerebral palsy children.